New dark species of the bee genus Colletes (Hymenoptera, Colletidae) from Mexico and Guatemala - Balboa, Carlos; Hinojosa-Díaz, Ismael; Ayala, Ricardo (Zootaxa, 2017)
Eight new species of Neotropical Colletes (Hymenoptera, Colletidae, Colletinae) are described and illustrated, Colletes tzotzilis Balboa & Ayala sp. n., C. jobeli Balboa & Ayala sp. n., C. guatemalensis Balboa & Ayala sp. n., C. chiapensis Balboa & Ayala sp. n., C. jaliscoensis Balboa & Ayala sp. n., C. nigerrima Balboa & Ayala sp. n., C. isabelae Balboa & Ayala sp. n. and C. solari Balboa & Ayala sp. n. A key to all known dark Mesoamerican species is provided.